10 State dissociation and interoception in functional neurological disorder. Issue 8 (20th July 2020) - Pick, Susannah; Butler, Morgan; Rojas-Aguiluz, Maya; Nicholson, Timothy; Laura, H
Abstract : Objective/aims: Interoceptive differences have been proposed as an aetiological factor in functional neurological disorder (FND) but there is limited supportive evidence. Previous studies are few, have mixed findings and assessed only (objective) interoceptive accuracy, but not (metacognitive) interoceptive awareness. The aim of this study was to explore interoception in FND in greater detail, by assessing interoceptive accuracy and awareness in individuals with a range of FND presentations. As dissociative symptoms (e.g., depersonalisation, derealisation) are common in FND and could influence interoception, we sought to examine the effects of induced acute dissociation on interoception. We hypothesised that interoceptive accuracy/awareness would be impaired at baseline in FND relative to healthy controls, but that the differences would be exacerbated following dissociation induction. Methods: Twenty adults with FND were recruited from online FND support groups. Diagnosis was confirmed by medical documentation from a relevant healthcare professional. The FND group was compared to a group of 20 healthy controls recruited from online community groups. A modified heart-beat tracking task measured interoceptive accuracy (correct detection of heart beats) and awareness (confidence judgements). A control task involved counting visually presented geometric shapes. Both tasks were completed before and after a validated dissociation induction procedure (mirror-gazing). Results: The FND group reported elevated dissociation at baseline relative to controls (p<0.01) but this difference was larger following mirror-gazing (p<0.001). Interoceptive accuracy did not differ significantly between groups at baseline; however, the FND group had significantly lower accuracy scores following mirror-gazing (p<0.05). There was no effect of group on shape counting accuracy at either timepoint. Confidence ratings on the interoception and shape counting tasks were significantly lower at both timepoints in the FND group relative to controls (all p-values <0.05 or <0.01). Conclusions: Individuals with FND reported elevated dissociation both before and after a dissociation induction procedure, although this was exacerbated post-dissociation induction. In contrast, interoceptive accuracy was unimpaired at baseline, but impaired following dissociation induction, relative to controls. The FND group showed reduced metacognitive awareness for detection of bodily states and external (visual) stimuli. Future research should better determine the nature of interoceptive deficits in FND and assess the impact of dissociation on a range of cognitive and affective processes relevant to the disorder.